An Appication of Buddhamma Principles Inenhanching Thai Isaan Weaving in the Area of Nakha Sub-District, Mueang District, Udon Thani Province - Siripunyo (Silawatcharapol), Phramaha Sompoch; Sinthunok , Boonsong; Namket , Somdet (Journal of Modern Learning Development, 2021)
Objectives of this article are: 1) to study the principles of Dharma Dhammikattha in Theravada Buddhism; 2) to study the status of Isan Thai weaving in Nakha sub-district, Muang district, UdonThani province; Applied Buddhism principles to promote weaving of Isaan Thai fabrics in NakhaSubdistrict, Mueang District, UdonThani Province. It is a qualitative research. By studying information from documents and field To present research in descriptive and analytical manner The research results were found that Tithathammikatthana refers to the dhamma that is possible in order to obtain benefits in the present 4 ways: (1) the concession base to with the persistence of living by working (2) Arak Ksupta, with the righteous diligence of saving the wealth which is obtained. Way of deterioration of wealth Condition of weaving Thai Isan weaving in the area of ​​Nakha Subdistrict It is to promote and develop agricultural products, handicrafts, products, and community enterprises for quality and uniqueness. Create value for products and increase distribution channels, promote knowledge in public relations, marketing to increase competitiveness and increase income. Application of Buddhist principles to promote weaving of Isan Thai fabrics in Nakha sub-district area. Makes it diligent and wise To pursue a career for honesty Not self-persecution 2) Good quality of life 3) Saving as collateral when necessary 4) Good friendliness is the building of a prosperous business network.